Sustainable WAC a whole systems approach to launching and developing Writing Across the Curriculum programs - Cox, Michelle 1971-; Galin, Jeffrey R. 1961-; Melzer, Dan (National Council of Teachers of English, 2018)
"Introduces a theoretical framework for WAC program development that takes into account the diverse contexts of today's institutions of higher education, encourages strategic thinking, and integrates a focus on program sustainability"--Provided by publisher.